2017
DOI: 10.1155/2017/6145651
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CM082, an Oral Tyrosine Kinase Inhibitor, on Experimental Choroidal Neovascularization in Rats

Abstract: The aims of this study were to evaluate the effects of CM082 on the development of choroidal neovascularization (CNV) in a laser-induced CNV rat model and to determine the drug concentration in the ocular tissues. After the laser-induced CNV model was established in rats, CM082 was orally administered. The effects of CM082 on the CNV lesions were assessed using fundus fluorescein angiography (FFA), CNV histology, and retinal pigment epithelium- (RPE-) choroid-sclera eyecup analysis. The concentrations of CM082… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Preclinical studies in rats revealed that an oral administration of vorolanib could reduce CNV lesions in a laser-induced CNV rat model. 9 In this study, vorolanib dose-dependently inhibited the KDR phosphorylation of HUVECs, thus notably repressed VEGF-induced proliferation of HUVECs. Moreover, vorolanib was found to inhibit the tube formation of HUVECs, further suggesting its role in inhibiting angiogenesis.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Preclinical studies in rats revealed that an oral administration of vorolanib could reduce CNV lesions in a laser-induced CNV rat model. 9 In this study, vorolanib dose-dependently inhibited the KDR phosphorylation of HUVECs, thus notably repressed VEGF-induced proliferation of HUVECs. Moreover, vorolanib was found to inhibit the tube formation of HUVECs, further suggesting its role in inhibiting angiogenesis.…”
Section: Discussionmentioning
confidence: 47%
“…Vorolanib (CM082) is a TKI that targets all VEGFR and plateletderived growth factor receptor (PDGFR) isoforms. 9 It has a shorter half-life and limited tissue accumulation compared with other TKIs. 10 Enhanced chemotherapeutic drug efficacy has also been shown by inhibition of the drug efflux function of ABCG2, a potential ATP-binding cassette transporter.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have indicated that vorolanib has a shorter half-life than approved TKIs for advanced RCC sunitinib and pazopanib. Furthermore, vorolanib is known to exert substantial inhibitory effects on VEGFR, PDGFR, c-KIT, and FLT-3, thus leading to the inhibition of vascular endothelial cell proliferation and lumen formation in vitro ( 16 , 17 ). The inhibition of VEGF signaling has been shown to induce the regression of choroidal neovascularization in a rat model treated with vorolanib ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vorolanib is known to exert substantial inhibitory effects on VEGFR, PDGFR, c-KIT, and FLT-3, thus leading to the inhibition of vascular endothelial cell proliferation and lumen formation in vitro ( 16 , 17 ). The inhibition of VEGF signaling has been shown to induce the regression of choroidal neovascularization in a rat model treated with vorolanib ( 17 ). A subsequent phase I dose-escalation trial in patients with neovascular age-related macular degeneration showed a favorable toxicity profile when administered with a daily dose of 200 mg of vorolanib in the vast majority of patients who completed 24-week treatment reported maintained or improved visual acuity ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…All animals received were cared for in strict accordance with the Association for Research in Vision and Ophthalmology Statement for the use of animals in vision and ophthalmic research and the Shanghai Tenth People's Hospital Guidelines for the Use of Animals in Research. Brown Norway rats (6-8 w, 180-200 g, male) were used to establish CNV models, and laser photocoagulation-induced CNV models were established as previously described [32]. Intraperitoneal injection of 1% pentobarbital sodium (40 mg/kg, Sigma-Aldrich) was used to anesthetize the animals, a topical application of 0.5% tropicamide (Mydrin-P, Santen Pharmaceutical Co., Osaka, Japan) was used to dilate the pupil, and 0.5% Alcaine (Alcon [China] Ophthalmic Product Co., Beijing, China) was used to anesthetize the ocular surface.…”
Section: Laser-induced Cnv In Ratsmentioning
confidence: 99%